Role Perceived ValueAs the Mediating Variable of The Effect of Service Quality on User Satisfaction (Study on KRI Operations At the Military Seaborne Command) - Widyo Sasongko; Yosi Pahala; Adenan Suhalis (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2022)
Quality of service in general greatly affects the satisfaction of its users. Synopsis In this thesis, we conduct research on service quality on user satisfaction in KRI operations at the Military Cross-Sea Command. This thesis uses a quantitative research method based on preliminary data, a structural equation model, used to examine data sourced from the Military Maritime Command. The conclusions from this study are that Perceived Value is influenced by the Quality of Service for KRI Kolinlamil users.